Study of Antibiotic Resistance in E. Coli Against Allopathic Drugs as Compared To Natural Herbs - Loyi Lego, Rimmo (Journal of Scientific Exploration, 2023)
The Rising Incidents of Antibiotic Resistance has been increasing at an exponential rate in recent years, and since it is often caused by rampant misuse of drugs such as Penicillin, many bacterial species such as E. coli have been able to mutate and gain Multi-Drug Resistance and Extended Drug Resistance (XDR) - to form what is otherwise known as Superbugs. The main purpose of the research is to investigate the efficacy of Allopathic Drugs as Compared to Natural herbs in treating pathogenic bacterial colonies, so as to find an alternative to reduce antibiotic resistance. Using experimental analysis, this study analysed the effectiveness of the allopathic drugs and natural herbs, in treating an E. coli culture. The experiment was carried out over a span of 14 days, with readings taken on every consecutive 2-day period. The efficacy was measured with respect to the zone of inhibition, and the results were compared for any form of resistance developed. The Allopathic drug, Azithromycin, as hypothesized was found to be the most effective in treating the E. coli culture, but a few resistant strains were observed. However, natural herbs like Tea tree oil were not far behind, and only a few colonies of E. coli showed resistance against them. Erythromycin and Garlic were not found to be as effective. This study answers the questions on alternatives to allopathic drugs and resistance to different substances. Further studies are however needed to establish the mechanism of resistance to these substances and to develop preventative measures